(untitled) (Bangladesh Journal of Medical Science, 2016)
Objective: Patient education is the process of enhancing patients knowledge and skills in order to encourage the required attitude and behaviors for maintaining or improving their health. This study aims to explore the barriers and facilitators of patient education in clinical environments from the viewpoint of nursing students. Materials and Method: 78 senior and junior nursing students at Jahrom University of Medical Sciences formed the participants of this descriptive-cross-sectional study. The participants were selected based on the census method. The questionnaire used to collect data included questions about students demography, barriers (10 questions), and facilitators (10 questions) in patient education. Results: The most important barriers to patient education were lack of appropriate educational facilities (4.34±0.99), time limitation (4.31±1.10), and nurses inadequate knowledge and skills (4.29±0.59). The most important facilitators were enhancing the knowledge and skills of educator (4.49±0.50), raising the interest of the educator (4.44±0.74), and implementing of the education step-by-step (4.40±0.49). Conclusion: Patient education is an important part of patient care thus nursing teachers should be encouraged to incorporate patient education in the curriculum as part of the introduction of diseases, and stress such issues as evaluation of patients health literacy, familiarity with educational tools, and methods of enabling patients. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.471-476